Clinical performance of two visual scoring systems in detecting and assessing activity status of occlusal caries in primary teeth (2010)
This study aimed to compare the clinical performance of two sets of visual scoring criteria for detecting caries severity and assessing caries activity status in occlusal surfaces. Two visual scoring systems – the Nyvad criteria (NY) and the ICDAS-II including an adjunct system for lesion activity assessment (ICDAS-LAA) – were compared using 763 primary molars of 139 children aged 3–12 years. The examinations were performed by 2 calibrated examiners. A subsample (n = 50) was collected after extraction and histology with 0.1% red methyl dye was performed to validate lesion depth and activity. The reproducibility of the indices was calculated (kappa test) and ROC analysis was performed to assess their validity and related parameters were compared using McNemar’s test. The association between the indices and with the histological examination was evaluated using Spearman’s correlation coefficient (rs). Visual criteria showed excellent reproducibility both regarding severity (NY: 0.94; ICDAS-II: 0.91) and activity (NY: 0.90; LAA: 0.91). The NY and LAA showed good association in caries activity assessment (rs = 0.88; 95% CI = 0.86–0.89; p < 0.001). Nevertheless, considering only cavitated lesions, this association was not significant (p > 0.05). Concerning the severity, both indices presented similar validity parameters. At D2 threshold, the sensitivity was higher for NY (NY = 0.87; ICDAS = 0.61, p < 0.05). Regarding activity status, NY showed higher specificities and accuracies. In conclusion, NY and ICDAS-II criteria are comparable and present good reproducibility and validity to detect caries lesions and estimate their severities, but the LAA seems to overestimate the caries activity assessment of cavitated lesions compared to NY.